Modeling performance indicators of resilient pharmaceutical supply chain - Chitra Lekha Karmaker; Tazim Ahmed (Modern Supply Chain Research and Applications, 2020)
Purpose In the recent dynamic market, supply chain disruptions are rapidly increasing with varied customer demand, technological changes, uncertain pandemic events etc. To overcome the unexpected disruptions, supply chain of each business should be resilient and pharmaceutical supply chain (PSC) is no exception. Motivated by the challenges and unexpected pandemic disruptions, this paper aims to examine the performance indicators (PIs) of the resilient PSC and to predict the resilience level for a certain time period in the context of Bangladesh. Design/methodology/approach The aim of this paper presents a structured framework based on the Delphi method, fuzzy DEMATEL (Decision Making Trial and Evaluation Laboratory) and system dynamics (SD). The proposed methodology was validated using expert's inputs from the relevant field in Bangladesh. This study reveals the influential relationships of indicators and resilience level using fuzzy DEMATEL and SD to improve the resiliency. Findings Findings revealed that "Supply chain risk orientation", "Visibility", "Flexibility", "Agility in supply chain" and "Collaboration" are the top five influential performance indicators for resilient PSC. The cause and effect relationship found that "IT capability", "Flexibility", "Supply chain network design", "Resource availability", "Supply chain risk orientation" and "Velocity" were in cause category which play a vital role for establishing resilient supply chain. SD approach has developed a model for predicting the resilience level of the supply chain. Originality/value This work is one of the initial contributions in the literature that has targeted on the identification and analysis of the significant PIs and predicting the resilience level of the PSC.
Keywords: 650; Fuzzy DEMATEL; Performance indicators; Pharmaceutical industry; Supply chain resilience; System dynamics model